#### Answer

x$^3$

#### Work Step by Step

Simplify the expression by combining like terms.
27x$^3$-26x$^3$=(27-26)x$^3$=(1)x$^3=x$^3$

Published by
Pearson

ISBN 10:
0-13417-805-X

ISBN 13:
978-0-13417-805-9

x$^3$

Simplify the expression by combining like terms.
27x$^3$-26x$^3$=(27-26)x$^3$=(1)x$^3=x$^3$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.